A novel and rapid method to purify the human complement opsonin C3b from human plasma - Sichau, Jannik; Schmidt, Christoph Q. (Frontiers in Immunology, 2025)
Complement opsonin C3b is at the center of the complement cascade. All complement initiation pathways converge when convertases activate C3, converting it into the anaphylatoxin C3a and the opsonin C3b, which can attach to surfaces via its freshly exposed thioester moiety. C3b has several important functions and remains a focus of basic and translational research. C3b and its proteolytically processed derivatives iC3b and C3dg are important opsonins for different complement receptors on various immune cells. C3b is the initiation nucleus for the formation of the alternative pathway C3 convertase and C3b clusters act as gatekeepers for the activation of C5, which initiates the terminal pathway. High densities of surface-deposited C3b alter the substrate specificity of complement convertases from C3 to C5 activation. It remains unknown how C3b achieves the “C5 priming” necessary for this process. Further exploration of the functions of C3b is laborious, as it generally requires the purification of C3 from plasma/serum, subsequent conversion to C3b, and further purification. Therefore, we developed a rapid (three days) and efficient method that purifies C3b directly from blood sources, requiring fewer steps and reagents than previously published protocols. This method utilizes the newly exposed sulfhydryl group, which becomes accessible by converting C3 to C3b. The C3b purified by this method exhibits high purity and very high activity, as demonstrated by affinity measurements for several known C3b ligands, the formation and dissociation of the alternative pathway convertase, and the capacity to be regulated by FI.